2010
DOI: 10.1002/hyp.7912
|View full text |Cite
|
Sign up to set email alerts
|

Hydrograph separation and precipitation source identification using stable water isotopes and conductivity: River Ganga at Himalayan foothills

Abstract: Abstract:The observed retreat of several Himalayan glaciers and snow packs is a cause of concern for the huge population in southern Asia that is dependent on the glacial-fed rivers emanating from Himalayas. There is considerable uncertainty about how cryospheric recession in the Himalayan region will respond to climate change, and how the water resource availability will be affected. As a first step towards quantifying the contribution of glacier-melt water, hydrograph separation of River Ganga at Rishikesh i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
125
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(134 citation statements)
references
References 50 publications
7
125
2
Order By: Relevance
“…A comparison of the isotopic composition of glacier meltwater in the Saldur catchment with samples taken in other parts of the globe reveals the variability of dominant climatic conditions. Saldur glacier melt was more depleted compared to the Mafengu River, China (Yang et al, 2012), similar to the Ganga River catchment in the Himalayan foothills (Maurya et al, 2011) and in the Langtang and Dudh Kosi basins in Nepal Himalaya (Racoviteanu et al, 2013). However, it was heavier than that in the Wind River Range in the American Rockies (Cable et al, 2011) and a Central Andean catchment (Ohlanders et al, 2013) and, not surprisingly, much heavier than that found at the Imersuaq Glacier, West Greenland (Yde and Tvis Knudsen, 2004).…”
Section: Isotopic Composition Of Snow Snowmelt and Ice Meltmentioning
confidence: 78%
See 3 more Smart Citations
“…A comparison of the isotopic composition of glacier meltwater in the Saldur catchment with samples taken in other parts of the globe reveals the variability of dominant climatic conditions. Saldur glacier melt was more depleted compared to the Mafengu River, China (Yang et al, 2012), similar to the Ganga River catchment in the Himalayan foothills (Maurya et al, 2011) and in the Langtang and Dudh Kosi basins in Nepal Himalaya (Racoviteanu et al, 2013). However, it was heavier than that in the Wind River Range in the American Rockies (Cable et al, 2011) and a Central Andean catchment (Ohlanders et al, 2013) and, not surprisingly, much heavier than that found at the Imersuaq Glacier, West Greenland (Yde and Tvis Knudsen, 2004).…”
Section: Isotopic Composition Of Snow Snowmelt and Ice Meltmentioning
confidence: 78%
“…2a) indicating that waters originating from upstream sources mixed to give composite stream water (Dalai et al, 2002;Maurya et al, 2011). The slope of 7.9 of the δ 18 O-δ 2 H relationship of stream water in the Saldur River was similar to that of rainfall (Fig.…”
Section: Isotopic Composition Of Stream Water and Groundwatermentioning
confidence: 80%
See 2 more Smart Citations
“…The strength and frequency of WD over the last three decades has increased in western Himalayas and decreased in the central Himalayas. On the basis of the variation in the deuterium-excess (dexcess) values of Ganges River water at Rishikesh, it was suggested that a significant fraction of the snow-melt and icemelt components are derived from winter precipitation with a moisture source from the mid-latitude westerlies (Maurya et al, 2011). The impact of climate change on the frequency and magnitude of precipitation events in the tropics is still a matter of debate (Held and Soden, 2006;Wentz et al, 2007;Allan and Soden, 2008).…”
mentioning
confidence: 99%